A Study of the Form and Function of Cobo Fort in the Tidore Sultanate: Kajian Bentuk dan Fungsi Benteng Cobo di Kesultanan Tidore - Manullang, Abel Agustino; Mahanani, Nugrahadi; Husni, Amir (Indonesian Journal of Islamic History and Culture, 2025)
The Tidore Sultanate was one of the major kingdoms in North Maluku, serving as a supplier of cloves since the 16th century AD. The availability of spices in North Maluku led to European expansion. The presence of Europeans in North Maluku in the 16th century AD brought ideas and concepts related to defense systems and fortifications. Cobo Fortress became one of the Spanish defense structures located in the territory of the Tidore Sultanate. This study reveals the form and function of Cobo Fortress during the Spanish occupation of the Tidore Sultanate. It uses qualitative methods to describe and analyze objects based on primary and secondary data. In addition, this study uses an archaeological-historical approach that draws on history and cultural processes documented in written sources, using historical documents and then combining them with the results of the Cobo Fortress excavations to reconstruct past life. In identifying the form and function of Cobo Fortress, morphological analysis, technological analysis, and contextual analysis are used. The results of this study explain that Fort Cobo was octagonal in shape at the bastion and combined with a parallelogram for the body. Fort Cobo functioned as a lookout post, monitoring Spanish security against Dutch attacks, overseeing the clove trade, and overseeing the security of the local community.